Creación de franquicias de "Las corvinas de Don Jimmy" - Fiallos Gordón, Sandra Elizabeth (2013)
Ceviches y Corvinas Don Jimmy is a restaurant located in Mercado Central, Historical Center of Quito, in Av Pichincha and Esmeraldas street for more tan 60 years, it has many reports on television, newspaper and variety of customers. It's a business focused on customer service with a traditional product. This project aims to carry out the expansion of a family business by selling franchises. To begin this project and citing Mr. Guido Santillan " a franchise must have a self-image, if it don’t have you should create one" so "Corvinas Don Jimmy " must create a self-image, so the business can be closer to the consumer and become the first traditional typical food chain, maintaining the quality of service, products and improving processes and in this way contribute with gastronomic tourism in Ecuador. Gastronomic Tourism has take more fame in recent years around the world and Ecuador do not want to be left behind so many Ecuadorian chefs promote this part of tourism and what better for a family to be part of this great tourist movement…